PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 101 KECAMATAN PAYUNG SEKAKI PEKANBARU - Ardiana '; Zariul Antosa; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the lack of IPS students' learning achievement, as seen from the average value of students is 71.10. Of the 33 students who achieve grades above KKM just 16 students (48.50%), while students who have not reached the KKM many as 17 students (51.50%), the value specified KKM is 75. Based on these problems need to be done classroom action research by applying the method of role playing. This research aims to improve learning achievement of IPS Grade V Elementary School District of Umbrella Sekaki Pekanbaru 101 Academic Year 2014/2015. Role Playing is a planned learning activities designed to achieve specific educational goals and is one form of educational games used to describe the roles, attitudes, behaviors, values with the aim to live feelings, viewpoints and ways of thinking of others. Role Playing is a teaching model is derived from the individual and social dimensions of education. This method helps students find personal meaning in their social world and help students explore issues about the relationship between humans and to play a role. This study was conducted by two cycles for VB grade students of SD Negeri 101 Pekanbaru District of payung Sekaki numbered 33 people. At each cycle I and II consist of three meetings, which consists of two face to face meetings and one times daily test at the end of each cycle. Role Playing with the applied method, can improve learning achievement of IPS students, visible from improving student learning achievement of basic scores with an average of 71.10 increased by 24.20% to 76.80 in the first cycle, the second cycle of the elementary scores increased as much as 36.30% to 81.80. The percentage of teacher activity also increased, as seen from the percentage of the activity of teachers in the first cycle the first meeting of 72.22%, an increase in the second meeting becomes 91.66%, in the second cycle at the first meeting increased to 91.66%, and at the second meeting rising again to 100%. The percentage of student activity also increased, as seen from the percentage of student activity in the first cycle of the first meeting and 72.22% in the second meeting of the increase is 91.66%, in the second cycle at the first meeting be 91.66%, and at the second meeting increased to 100%. Based on the results of this study concluded that the application of the method of role playing can improve learning outcomes IPS Grade Elementary School VB 101 District of payung Sekaki Pekanbaru.Keywords : Role Playing Methods, Learning Achievement of IPS2